The Effect of Added Moringa Leaves (Moringa oleifera L.) and Quail Eggs (Coturnix-coturnix japonica) on Wingko as A Snack for Anemia - Fithri Yati Eka Nur Jannah; Asrul Bahar (International Journal on Food, Agriculture and Natural Resources, 2022)
This study aims to (1) determine the effect of adding moringa leaves and quail eggs to the preference level for wingko, which includes color, aroma, texture, and taste as snacks for anemia patients; (2) determine the nutritional value of the best product through wingko organoleptic test by examining the influence of adding moringa leaves and quail eggs. The research employed a pure experimental design using a 3x2 factorial design with 6 treatments. In this study, the K factor was used as the addition of moringa leaves with level 3, and the P factor was the addition of quail eggs with 2 levels. The results showed that: (1) wingko with the addition of 20% moringa leaves and 20% quail eggs was favored by the panelists based on the De Garmo test, with a productivity value of 0.88. By employing the Kruskal-Wallis test and Mann-Whitney test, this study has confirmed that the proportion of added moringa leaves and quail eggs affects the aroma, color, and taste of wingko; (2) the nutritional value of the best wingko contains 7.63% protein based on Kjeldah test, 43.97% carbohydrates based on Luff Schriool test, 12.45% fat based on direct extraction test, and 4.37 mg iron(Fe) as identified in atomic absorption spectrometer test; (3) the addition of 20% moringa leaf wingko and 20% quail eggs in 100 grams could meet the requirement of protein, carbohydrates, fat, and iron.